Novel contribution to clubfoot pathogenesis: The possible role of extracellular matrix proteins - Eckhardt, Adam; Novotny, Tomas; Doubkova, Martina; Hronkova, Lucia; Vajner, Ludek; Pataridis, Statis; Hadraba, Daniel; Kulhava, Lucie; Plencner, Martin; Knitlova, Jarmila; Liskova, Jana; Uhlik, Jiri; et al. (Journal of orthopaedic research, 2019)
Idiopathic pes equinovarus (clubfoot) is a congenital deformity of the feet and lower legs. Clubfoot belongs to a group of fibro-proliferative disorders but its origin remains unknown. Our study aimed to achieve the first complex proteomic comparison of clubfoot contracted tissue of the foot (medial side; n = 16), with non-contracted tissue (lateral side; n = 13). We used label-free mass spectrometry quantification and immunohistochemistry. Seven proteins were observed to be significantly upregulated in the medial side (asporin, collagen type III, V, and VI, versican, tenascin-C, and transforming growth factor beta induced protein) and four in the lateral side (collagen types XII and XIV, fibromodulin, and cartilage intermediate layer protein 2) of the clubfoot. Comparison of control samples from cadavers brought only two different protein concentrations (collagen types I and VI). We also revealed pathological calcification and intracellular positivity of transforming growth factor beta only in the contracted tissue of clubfoot. Most of the 11 differently expressed proteins are strongly related to the extracellular matrix architecture and we assume that they may play specific roles in the pathogenesis of this deformity. These proteins seem to be promising targets for future investigations and treatment of this disease. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res.
Keywords: kalcinóza; lidé; extracellular matrix; Mass Spectrometry; prospektivní studie; Female; dítě; clubfoot; Calcinosis; extracelulární matrix - proteiny; Transforming Growth Factor beta; pes equinovarus; Humans; Extracellular Matrix Proteins; transformující růstový faktor beta; Prospective Studies; předškolní dítě; Child, Preschool; Proteome; mužské pohlaví; collagen; proteomics; proteom; Clubfoot; ženské pohlaví; fibrosis; Male; Child; hmotnostní spektrometrie